2012
DOI: 10.1212/wnl.0b013e31825830bd
|View full text |Cite
|
Sign up to set email alerts
|

White matter imaging contributes to the multimodal diagnosis of frontotemporal lobar degeneration

Abstract: Objective: To evaluate the distribution of white matter (WM) disease in frontotemporal lobar degeneration (FTLD) and Alzheimer disease (AD) and to evaluate the relative usefulness of WM and gray matter (GM) for distinguishing these conditions in vivo.Methods: Patients were classified as having FTLD (n ϭ 50) or AD (n ϭ 42) using autopsy-validated CSF values of total-tau:␤-amyloid (t-tau:A␤ 1-42 ) ratios. Patients underwent WM diffusion tensor imaging (DTI) and volumetric MRI of GM. We employed tract-specific an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
69
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 35 publications
8
69
2
Order By: Relevance
“…These areas are implicated in both FTLDtau and FTLD-TDP. 22,32,35,36 We previously found that lower copy numbers of rs1768208 MOBP risk allele are associated with reduced FA in SLF in a clinically mixed cohort; however, this was in a more posterior and superior region than in the current study of sporadic bvFTD. 11 Additional work is needed to further investigate these imaging findings.…”
contrasting
confidence: 70%
“…These areas are implicated in both FTLDtau and FTLD-TDP. 22,32,35,36 We previously found that lower copy numbers of rs1768208 MOBP risk allele are associated with reduced FA in SLF in a clinically mixed cohort; however, this was in a more posterior and superior region than in the current study of sporadic bvFTD. 11 Additional work is needed to further investigate these imaging findings.…”
contrasting
confidence: 70%
“…These studies suggested that on average there is reduced FA in the anterior corpus callosum of FTLD and reduced GM in the precuneus and posterior cingulate of AD. 7,8 While the neuroanatomic distribution of disease that contributed to classification in prior studies could be confounded by the clinical heterogeneity of the samples, the current study observed similar regions contributing to pathologic heterogeneity in a single clinical syndrome. Specifically, anterior corpus callosum WM and precuneus and posterior cingulate GM appear also to differentiate CBS-non-AD and CBS-AD.…”
Section: )mentioning
confidence: 50%
“…Our findings also converge with 2 studies suggesting that reduced WM integrity in the corpus callosum is associated with CBS 21 and is sensitive and specific for detecting FTLD relative to AD pathology. 7,8 In one prior neuroimaging report of autopsy-confirmed corticobasal degeneration, GM disease was seen in posterior and superior frontal, insula, and supplementary motor regions, and WM disease was seen in the corpus callosum and external capsule. 22 While this study used both GM and WM imaging, this work differs from ours by assessing volumetric measures of WM rather than DTI.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies performed whole brain analysis , McMillan, Brun et al 2012, Pettit, Bastin et al 2012, Prudlo, Bissbort et al 2012, Sarica, Cerasa et al 2014. Whole brain TBSS found significant changes in FA and MD in the SLF bilaterally (Sarica, Cerasa et al 2014.…”
Section: Whole Brain Analysismentioning
confidence: 99%